2012
DOI: 10.1021/cb300094a
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting Antibacterial Peptide Inhibitor of Early Lipid A Biosynthesis

Abstract: UDP-3-O-(R-3-hydroxyacyl)GlcN N-acyltransferase (LpxD) has been shown to be essential to survival of lipid A producing Gram-negative bacteria. In this study, LpxD-binding peptides 12 amino acids in length were identified from a phage-bound random peptide library screen. Three peptides displayed antibacterial activity when expressed intracellularly, one of which (RJPXD33) represented 15% of the total hits. RJPXD33 binds to E. coli LpxD with a Kd of 6 μM and is competitive with R-3-hydroxymyristoyl-ACP binding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…When the assay was performed with EcLpxA, the observed K d for FITC-RJPXD33⌬6 was 12 Ϯ 1 M (Table 2). This value was in close proximity to the previously published value (K d ϭ 17 Ϯ 1.6 M) for the full-length FITC-RJPXD33 (13). This suggested that the six terminal amino acids are not making extensive binding contacts to LpxA, in agreement with the crystal structure.…”
Section: Comparison Of Rjpxd33 Binding With (R)-␤-hydroxylauroyl-supporting
confidence: 89%
See 4 more Smart Citations
“…When the assay was performed with EcLpxA, the observed K d for FITC-RJPXD33⌬6 was 12 Ϯ 1 M (Table 2). This value was in close proximity to the previously published value (K d ϭ 17 Ϯ 1.6 M) for the full-length FITC-RJPXD33 (13). This suggested that the six terminal amino acids are not making extensive binding contacts to LpxA, in agreement with the crystal structure.…”
Section: Comparison Of Rjpxd33 Binding With (R)-␤-hydroxylauroyl-supporting
confidence: 89%
“…by phage display against immobilized LpxD (13). Although no EcLpxD-RJPXD33 structure is available, this current work suggests that RJPXD33 would overlap with the acyl-PPan arm of acyl-ACP, thereby inhibiting acyl-ACP from binding to LpxD.…”
Section: Peptide (Sequence)mentioning
confidence: 88%
See 3 more Smart Citations